Hấp phụ Cr(VI) trong môi trường nước bằng Vật liệu hấp phụ bã chè biến tính KOH - Hương, Đỗ Trà; Thành, Đặng Văn; Khuê, Mai Quang; Kim Ngân, Nguyễn Thị (Vietnam Journal of Chemistry, 2016)
The KOH-modified tea residue (KTR) was used as a adsorbent to remove efficiently Cr(VI) from aqueous solution. Scanning electron microscopy (SEM) images of KTR reveal a highly porous surface structure of the adsopbent. The adsorption properties for Cr(VI) of KTR were investigated by batch method. The influence of pH (1–8), contact time (30-180 min), and the amount of adsorbent (0.01-0.05 g) on Cr(VI) removal efficiency by the  KRT were also determined. The results show that the time to reach adsorption equilibrium, the optimal pH value, and mass of adsopbent are 150 min, 1.0, and 0.15 g, respectively. The maximum monolayer adsorption capacity of KTR is 52,083 mg/g. KTR acts as a promising adsorbent for the removal of heavy metal ions from aqueous solution. Keywords. Adsorption, tea waste residue, Langmuir isotherm, heavy metals, ankali treated tea residue